Early diagnosis of traumatic intracranial hematomas - Ayaz, Hasan (J Biomed Opt, 2019)
Timing of the intervention for intracranial hematomas is critical for its success, specifically since expansion of the hemorrhage can result in debilitating and sometimes fatal outcomes. Led by Britton Chance, we and an extended team from University of Pennsylvania, Baylor and Drexel universities developed a handheld brain hematoma detector for early triage and diagnosis of head trauma victims. After obtaining de novo Food and Drug Administration clearance, over 200 systems are deployed in all Marine battalion aid stations around the world. Infrascanner, a handheld brain hematoma detection system, is based on the differential near-infrared light absorption of the injured versus the noninjured part of brain. About 12 independent studies have been conducted in the USA, Canada, Spain, Italy, the Netherlands, Germany, Russia, Poland, Afghanistan, India, China, and Turkey. Here, we outline the background and design of the device as well as clinical studies with a total of 1293 patients and 203 hematomas. Infrascanner demonstrates high sensitivity (adults: 92.5% and children: 93%) and specificity (adults: 82.9% and children: 86.5%) in detecting intracranial hematomas [Formula: see text] in volume and [Formula: see text] from the surface of the brain. Infrascanner is a clinically effective screening solution for head trauma patients in prehospital settings where timely triage is critical.